2014
DOI: 10.4081/gh.2014.43
|View full text |Cite
|
Sign up to set email alerts
|

Hospital distribution in a metropolitan city: assessment by a geographical information system grid modelling approach

Abstract: Abstract. Grid models were used to assess urban hospital distribution in Seoul, the capital of South Korea. A geographical information system (GIS) based analytical model was developed and applied to assess the situation in a metropolitan area with a population exceeding 10 million. Secondary data for this analysis were obtained from multiple sources: the Korean Statistical Information Service, the Korean Hospital Association and the Statistical Geographical Information System. A grid of cells measuring 1 × 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…A study in Japan identified scarcity of healthcare resources in low socioeconomic population groups, an imbalance in healthcare services provision, and a positive correlation between hospital bed density and inpatient flow ratio [54]. An association between highway and major arterial roads, number of subway entrances, and row house areas with hospital distributions in a metropolitan city was also reported [55]. The different analytical approaches applied in our study clearly demonstrated the inequality in hospital and hospital beds concentrations.…”
Section: Discussionsupporting
confidence: 54%
“…A study in Japan identified scarcity of healthcare resources in low socioeconomic population groups, an imbalance in healthcare services provision, and a positive correlation between hospital bed density and inpatient flow ratio [54]. An association between highway and major arterial roads, number of subway entrances, and row house areas with hospital distributions in a metropolitan city was also reported [55]. The different analytical approaches applied in our study clearly demonstrated the inequality in hospital and hospital beds concentrations.…”
Section: Discussionsupporting
confidence: 54%
“…For this reason, the location of public facilities becomes a central factor in the quality of life of populations and in guaranteeing an appropriate redistribution of public funds (Witter, 2012). The problem is thus generally centred around reducing spatial friction (Hyndman and Holman, 2001;Lee and Moon, 2014), but this concern is gradually replaced by others as one comes closer to defining the specific location area. The reason is that one has to consider the compatibility of the facility with the characteristics of a location option (urban dynamics, noise, pollution, congestion, availability of space, environmental sensitivity, etc.)…”
mentioning
confidence: 99%